Valuation of local coastal community willingness to participate in marine debris adaptation within Nusa Penida marine protected area - Zahra Sakinah; Suhardono Sapta; Suryawan I Wayan Koko (BIO Web of Conferences)
This research investigates the factors influencing community willingness to participate in marine debris management programs in Nusa Penida, Indonesia, focusing particularly on various demographic variables. Employing a sample size of 60 respondents, the study utilized Chi-square tests and regression analysis to explore the association between willingness to participate and factors such as age, gender, income, education level, marital status, and employment. The results revealed no statistically significant influence of these demographic variables on participation willingness, except for a suggestive trend in age-related participation. Based on these findings, an action plan was developed to enhance community engagement across different age groups through tailored strategies. This approach includes the integration of technology, flexible scheduling, and targeted educational campaigns to accommodate and leverage the unique capacities and motivations of each age segment. The study highlights the importance of demographic considerations in designing effective community-based environmental initiatives and provides a framework that can be adapted for similar conservation efforts globally.